Keluhan Carpal Tunnel Syndrome Pada Pengrajin Purun - Lucy Puspita; Arifin Arifin; Junaidi junaidi; Muhammad Pahruddin (Poltekkes Kemenkes Banjarmasin Jurusan Kesehatan Lingkungan Banjarbaru, 2022)
Carpal Tunnel Syndrome includes disorders of the muscles, nerves, tendons, and blood vessels caused by repetitive activities for a long time. One of the informal sectors that always works using hands and wrists is the purun craftsman in Palam, Cempaka, Banjarbaru City. The purpose of this study was to determine the relationship between length of service and tenure with complaints of CTS on Purun craftsmen. One of the sampling techniques used is purposive sampling using inclusion and exclusion criteria. The number of samples collected is 53 respondents. Data analysis using the chi-square test. The results of the research test on the variable length of work, the Pearson chi-square sig value of 0.002 (<0.05) indicates a relationship between length of work and complaints of carpal tunnel syndrome in craftsmen. Although the results of the time-of-use survey test vary, the results of the research test on the variable period of service, the value of sig pearson's chi-square sig 0.002 (etlt; 0.05), which means that there is a relationship between years of service and complaints of carpal tunnel syndrome of purun craftsmen in Palam, Cempaka, Banjarbaru City.